Unpacking moving: A quantitative spatial equilibrium model with wealth - Elisa Giannone; Qi Li; Nuno Paix\~ao; Xinle Pang (Bank of Canada, 2023)
We argue that the interaction between mobility and wealth provides a view that rationalizes low geographic migration rates, despite migration costs being lower than currently thought. We reach this conclusion by developing and solving a quantitative dynamic spatial equilibrium model with endogenous wealth accumulated through liquid and illiquid assets. We estimate a yearly moving cost between Canadian cities of 196,303 CAD for an average adult, substantially lower than previous estimates. To demonstrate the model's validity, we study policies advocated to reduce disparities: Do moving vouchers or housing affordability policies enhance welfare, especially for the poor? Our findings suggest that moving vouchers only marginally increase the welfare of eligible households, and those who receive the vouchers tend to move to locations with lower house prices and wages. In contrast, our model shows that lower housing regulations in Vancouver can decrease the welfare gap between rich and poor by lowering house prices nationwide through spatial reallocation. Thus, the insurance value of living in high-income cities becomes higher, reducing the incentive for low-wealth families to move precautionarily to locations with low housing costs.
Keywords: G51; R12; R13; R2; R31; R52; 330; Housing; Regional economic developments